Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(b,8-|x-7|=2\)
\(|x-7|=6\)
\(\Rightarrow\orbr{\begin{cases}x-7=6\\x-7=-6\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=13\\x=1\end{cases}}\)
\(3x+2\left(-2\right)^3=-\left(-2\right)^3\)
\(\Leftrightarrow3x+2\cdot\left(-8\right)=-8\)
\(\Leftrightarrow3x-16=-8\)
\(\Leftrightarrow3x=8\)
\(\Leftrightarrow x=\frac{8}{3}\)
4x-15=-75-x
\(\Leftrightarrow4x+x=-75+15\)
\(\Leftrightarrow5x=-60\)
\(\Leftrightarrow x=-12\)
a,\(15-\left(-4-x\right)=6\)
\(\Leftrightarrow-4-x=15-6\)
\(\Leftrightarrow-4-x=9\)
\(\Leftrightarrow x=-4-9\)
\(\Leftrightarrow x=-13\)
b,\(-30+\left(25-x\right)=-1\)
\(\Leftrightarrow25-x=-1-\left(-30\right)\)
\(\Leftrightarrow25-x=29\)
\(\Leftrightarrow x=25-29=-4\)
c,\(x-\left(12-25\right)=-8\)
\(\Leftrightarrow x+13=-8\)
\(\Leftrightarrow x=-21\)
e,\(x-5=1\Rightarrow x=6\)
g,\(x+30=-4\)
\(\Leftrightarrow x=-4-30\)
\(\Leftrightarrow x=-34\)
h,\(x-\left(-24\right)=3\)
\(\Leftrightarrow x+24=3\)
\(\Leftrightarrow x=3-24\)
\(\Leftrightarrow x=-21\)
i,\(\left(x+5\right)+\left(x-9\right)=x+2\)
\(\Leftrightarrow x+5+x-9-x-2=0\)
\(\Leftrightarrow x-6=0\)
\(\Leftrightarrow x=6\)
k,\(\left(27-x\right)+\left(15+x\right)=x-24\)
\(\Leftrightarrow27-x+15+x-x+24=0\)
\(\Leftrightarrow-x+66=0\)
\(\Leftrightarrow-x=-66\)
\(\Leftrightarrow x=66\)
a) 15-(-4-x)=6
15 + 4 + x = 6
19 + x = 6
x = 6 - 19
x = 6 + ( -19 )
x = -13
b) -30+( 25- x ) =-1
25- x = -1 - ( - 30 )
25- x = -1 + 30
25- x =29
x = 25 - 29
x = 25 + ( -29 )
x = -4
c) x- ( 12-25) =-8
x - ( - 13 ) = -8
x + 13 = -8
x = -8 - 13
x = -8 + ( -13 )
x = - 21
d) ( x-29 ) - (17- 38 ) = -9
( x-29) - (-21 ) = -9
x -29 = -9 + ( -21 )
x -29 = -30
x = -30 + 29
x = -1
e) x-5=1
x = 1 + 5
x = 6
g) x + 30 = -4
x = -4 - 30
x = -4 + ( -30 )
x = -34
h) x- ( -24 ) = 3
x = 3 + ( -24 )
x = -21
l) 22- ( - x ) = 12
-x = 22 - 12
-x = 10
x = -10
i) ( x + 5 ) + ( x - 9 ) = x + 2
x + 5 + x - 9 = x + 2
x + x + ( 5 - 9 ) = x + 2
x + x + ( -4 ) = x + 2
x + x = x + 2 - ( -4 )
x + x = x + 2 + 4
x + x =x + 6
=> x = 6
a, Ta có : \(x-5=-1\)
\(\Leftrightarrow x=\left(-1\right)+5\)
\(\Rightarrow x=4\)
Vậy \(x=4\)
b, Ta có :\(x+30=-4\)
\(\Leftrightarrow\left(-4\right)-30\)
\(\Leftrightarrow x=\left(-34\right)\)
Vậy \(x=\left(-34\right)\)
c, Ta có : \(x-\left(-24\right)=3\)
\(x=3+\left(-24\right)\)
\(\Leftrightarrow x=\left(-21\right)\)
Vậy \(x=\left(-21\right)\)
d,Ta có : \(22-\left(-x\right)=12\)
\(\Leftrightarrow\left(-x\right)=22-12\)
\(\Leftrightarrow\left(-x\right)=10\)
Vậy ....
a. 250 - 10 ( 24 - 3x) : 15 = 244
10 ( 24 - 3x) : 15 = 250 - 244
10 ( 24 - 3x) : 15 = 6
10 ( 24 - 3x) = 15 .6
10 ( 24 - 3x) = 90
( 24 - 3x) = 90 : 10
( 24 - 3x) = 9
3x = 24 - 9
3x =15
x = 15 : 3
x = 5
bạn ơi sai rồi 30%-x +x-15
=0,3-(x-x)-15
=0,3-0-15
=-14,7
chứ làm sao mà bằng -67 đc